KETERKAITAN INDEKS SAHAM DUNIA TERHADAP JAKARTA ISLAMIC INDEX - Suripto Suripto; Desri Ayu Puspita; Surpiyanto Surpiyanto (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2019)
This research is aim to determine correlation world stock index and Indonesian stock index on Jakarta Islamic Index (JII) (2013-2017). Jakarta Islamic Index is dependent variable and the independent variabel Dow Jones Islamic Market (DJIM), Dow Jones Industrial Average (DJIA), Jakarta Stock Exchange and Indonesia Sharia Stock Index (ISSI). The data was taken Index around 5 years with the total of population are 60 companies. The results showed DJIM, DJIA and ISSI related to JII, and Jakarta Stock Exchange did not relate to JII.